The Two-Face of Anies Baswedan: The Inconsistency with Regards to Jakarta Reclamation - Jean Antunes Rudolf Zico (Journal of Language and Literature, 2020)
Homo homini lupus and the end justifies the means are two general adagios that have been applied in the political contestation. The main idea behind the two adagios is that one should benefit any means necessary at all cost in order to execute the vested political agenda. Such practice is almost found in any domain of political practice, especially in the general election for governor. One of the good examples that describes the case best is the governor election of DKI-1. During this election, one of the candidates, namely Anies Baswedan, has successfully manipulated the environmental issues, namely Jakarta Reclamation, into one of his political weapons by promising that he shall cease Jakarta Reclamation if he has been officially elected as the Governor of Jakarta Special Capitol. Indeed, he has won the election and thus he has kept his commitment by sealing the 932 buildings from Island D. However, several moments later he issued the building permit for a number of buildings in one of the reclamation islands and ever since then people, especially his supporters, have started questioning his commitment toward the cessation of Jakarta Reclamation. Departing from the case, the researcher is encouraged to conduct a study that might disclose the true characteristics of a political figure. Within the conduct of the study, the researcher took a number of statements from the online news portals that have been considered trustworthy and reputable in portraying certain events especially the political ones and at the same time analysed these statements by applying the Fairclough analysis and four questions of critical paradigm. The results of the study show that: (a) Anies Baswedan has not fully kept his commitment toward the cessation of Jakarta Reclamation; and (b) the four questions of critical paradigm might be implemented for criticizing a political figure with several modifications.